2021
DOI: 10.3390/molecules26164965
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine Increases the Production of Antioxidant Phenolic Acids in Ginkgo biloba Cell Cultures

Abstract: The aims of this study were to evaluate the antioxidant properties, to investigate the content of major secondary metabolites in Ginkgo biloba cell cultures, and to determine the change in the production of phenolic acids by adding phenylalanine to the culture medium. Three in vitro methods, which depend on different mechanisms, were used for assessing the antioxidant activity of the extract: 1,1-diphenyl-2-picrylhydrazil (DPPH), reducing power and Fe2+ chelating activity assays. The extract showed moderate ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 55 publications
0
10
0
2
Order By: Relevance
“…Phenylalanine concentration 0.75 g/L highly stimulated quercetin production in a callus culture of Abutilon indicum [ 43 ]. In cell cultures of Ginkgo biloba increased levels of gallic, protocatechuic and p-hydroxybenzoic acids were detected after administration of 0.66–1.33 g/L Phe [ 44 ]. Verbascoside biosynthesis, in contrast, was activated in cell suspension cultures of Buddleja cordata by the addition of 100 mg/L of Phe [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Phenylalanine concentration 0.75 g/L highly stimulated quercetin production in a callus culture of Abutilon indicum [ 43 ]. In cell cultures of Ginkgo biloba increased levels of gallic, protocatechuic and p-hydroxybenzoic acids were detected after administration of 0.66–1.33 g/L Phe [ 44 ]. Verbascoside biosynthesis, in contrast, was activated in cell suspension cultures of Buddleja cordata by the addition of 100 mg/L of Phe [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the study on the accumulation of bioactive metabolites in agitated cultures of Scutellaria lateriflora , authors used various concentrations of the precursor PheAla (1–2.5 g/L) and found that the optimal concentration of phenylalanine that did not cause inhibition of biomass growth was 1.5 g/L [ 15 ]. Skrzypczak-Pietraszek E. et al confirmed that a phenylalanine concentration of 1.6 g/L was the most advantageous in agitated cultures of Vitex agnus castus [ 16 ]. On the other hand, Szopa et al proved that, at concentrations in the range of 0.0165–0.165 g/L, phenylalanine did not inhibit the increase in the biomass of agitated cultures of two Aronia spp., while, at higher concentrations (0.825–1.65 g/L), it inhibited biomass growth [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a study on Rhodiola imbricata cell suspension cultures, the addition of phenylalanine at different concentrations (0.5–3 mM) caused an increase in the production of rosavin, rosarin, and p -coumaric acid [ 38 ]. In a study on V. agnus castus shoot cultures, the addition of phenylalanine at a dose of 1.6 g/L led to increased production of phenolic acids and flavonoids [ 16 ]. In a study of S. lateriflora shoot cultures, feeding with phenylalanine at a concentration of 1.5 g/L was found to be the best strategy to increase the production of flavonoids and verbascoside [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the monocotyledonous plant suspension cells reported include Veratrum california , Vanilla planifolia , Fritillaria cirrhosa , Dioscorea deltoidea , and Crocus sativus , etc. Gymnosperms are more difficult to induce than angiosperms because they are less sensitive to induction, and only few reports have been published so far, such as Taxus chinensis , Ginkgo biloba , Pinus pinaster . Taxus transgenic suspension cells have obtained a large amount of paclitaxel, a secondary metabolite with anticancer activity …”
Section: Suspension Cell Systems Of Plantsmentioning
confidence: 99%